"He May Do Harm . . .": Translation and Meaning of 2 Sam 12.18. Issue 3 (December 2020) - Jones, Ethan
Three major English translations, NRSV, ESV, and NASB, render וְאֵיךְ נֹאמַר אֵלָיו מֵת הַיֶּלֶד וְעָשָׂה רָעָה׃‎ as "How then can we tell him the child is dead? He may do himself some harm." These translations insert the reflexive pronoun "himself" as the object of עשׂה‎. While such a reading is possible, it is not at all probable when we take into account how reflexives are expressed in Biblical Hebrew, as well as the syntax and semantics of עשׂה‎. This article contributes to our understanding of 2 Sam 12.18 not by offering a new translation of וְעָשָׂה רָעָה‎, but by providing a linguistic explanation for why translators should reject the reflexive "harm himself" and instead render the phrase as "he may do harm" (so MEV).